My Waste, My Responsibility: Waste Management Education for Students in Elementary School - Darman Manda; Dyan Paramitha Darmayanti; Sulmiah Sulmiah; Maya Kasmita; Asri Nur Aina (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
The ‘My Waste, My Responsibility’ socialisation was held at SD Negeri Tamalanrea, Makassar, on 29 May 2024, aiming to raise the awareness of students, teachers, and parents about the importance of good and proper waste management. This activity involved students from various levels, teachers, and 7th year Teaching Campus students as facilitators. The methods used include the delivery of educational materials, video playback, and direct waste sorting simulations. The results of the activity showed an increase in students' understanding in sorting organic and inorganic waste and an increase in the involvement of teachers and parents in supporting this good habit. However, some challenges are still faced, such as differences in students' level of understanding and limited waste management facilities at school. It is recommended to integrate learning related to environmental hygiene in the school curriculum, improve waste sorting facilities, and conduct regular monitoring to ensure the sustainability of the socialisation results. This socialisation is an important first step in creating a sustainable hygiene culture in schools.